NanoTraPPED—A New Method for Determining the Surface Energy of Nanoparticles via Pickering Emulsion Polymerization - Andrei Honciuc; Oana-Iuliana Negru (Nanomaterials, 2021)
Surface energy with its polar and disperse components describes the physicochemical state of nanoparticles’ (NPs) surfaces, and can be a valuable parameter for predicting their bulk behavior in powders. Here, we introduce a new method, namely, Nanoparticles Trapped on Polymerized Pickering Emulsion Droplets (NanoTraPPED), for measuring the surface energy of a series of silica NPs bearing various surface functional groups. The method consists in creating Pickering emulsions from vinyl bearing monomers, immiscible with water, whereas NPs of interest have a stabilizing role, and in the process, become trapped at the monomer/water interface of emulsion droplets. The Pickering emulsion is polymerized, and polymer microspheres (colloidosomes) decorated with NPs are obtained. NanoTraPPED relies on measuring contact angles from the immersion depth of nanoparticles at the interface of various polymer colloidosomes with the electron microscope. The contact angle values are used as input for the Owens-Wendt-Rabel-Kaelble (OWRK) model, to quantitatively determine the total surface energy with water γNP/water, air γNP, and the corresponding polar and dispersive interaction components of NPs carrying -NH2, -SH, -OH, -CN and -C8 surface functional groups, ranking these according to their polarity. Our findings were confirmed independently by calculating the interfacial desorption energies of NPs from contact angles.